Keeping themselves alive: Identifying and analysing Queen’s musical development, 1973–1980 - Braae, Nick (Popular Music History, 2016)
This article is a study of British rock band Queen’s output between 1973 and 1980. It traces the changes in the band’s music through this era with respect to the notion of musical development. I consider Queen’s songs from three perspectives—style, the group’s cumulative idiolect, and the role of idiolect traits within songs—to suggest that each vantage point produces a different reading of Queen’s career trajectory. I further argue that the most appropriate reading of Queen’s development is in terms of an ‘expedition’ narrative, whereby the group explored new stylistic ground but marked these expeditions with the traits of its idiolect. Queen’s development is thus not a singular path from one point to another, but rather a wide-ranging musical journey with the group’s sonic imprint impressed on each stylistic turn.